SOCIAL SECURITY: THE SPECIAL INSURED - Moreira da Veiga Pessoa, Bruno (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to present an analysis of the condition of Special Insured in the Brazilian legal system. Its historical evolution as a social debt with those who were and are most responsible for feeding the country. Introduce the legal concept of Special Insured, analyze the requirements for granting the special Insured’s retirement and the means of proof of the time of rural activity.